2016
DOI: 10.1021/acs.analchem.6b00731
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Structural Effects of Epigallocatechin-3-gallate and Dopamine Binding to α-Synuclein

Abstract: The intrinsically disordered and amyloidogenic protein -synuclein (AS) has been linked to several neurodegenerative states, including Parkinson's disease. Here, nano-electrospray-ionization mass spectrometry (nano-ESI-MS), ion mobility (IM), and native top-down electron transfer dissociation (ETD) techniques are employed to study AS interaction with small molecules known to modulate its aggregation, such as epigallocatechin-3-gallate (EGCG) and dopamine (DA). The complexes formed by the two ligands under id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 66 publications
22
89
0
Order By: Relevance
“…Most importantly, it can be observed that the two ligands display different conformational selectivity, with EGCG preferentially binding to the low-charge protein component and DA to an intermediate component. [66] This different behavior is reflected in opposite structural effects of the two ligands, as detected by IM within individual charge states. [66] These results offer a rationale for the distinct biochemical effects of the two ligands.…”
Section: Comparison With Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, it can be observed that the two ligands display different conformational selectivity, with EGCG preferentially binding to the low-charge protein component and DA to an intermediate component. [66] This different behavior is reflected in opposite structural effects of the two ligands, as detected by IM within individual charge states. [66] These results offer a rationale for the distinct biochemical effects of the two ligands.…”
Section: Comparison With Solution Methodsmentioning
confidence: 99%
“…[66] This different behavior is reflected in opposite structural effects of the two ligands, as detected by IM within individual charge states. [66] These results offer a rationale for the distinct biochemical effects of the two ligands. Furthermore, the opposite trends observed for the two ligands under identical conditions, in either positive-or negative-ion mode, strongly suggest that the observed complexes reflect preexisting protein-ligand complexes rather than artifacts induced by the ESI conditions.…”
Section: Comparison With Solution Methodsmentioning
confidence: 99%
“…[193][194][195][196][197][198][199][200] Finally, ECD and ETD have proven to be so little disruptive toward peptide and protein structure that in addition to weak covalent bonds, even noncovalent interactions often survive the process. As a result, dissociation of protein-ligand complexes will often result in the detection of fragments that are still bound to the ligand, to allow identification of, for example, a ligand-binding site, [201][202][203][204][205] residues involved in a specific peptide/peptide interaction, 206 and mapping of a protein/peptide interface. 207 The preservation of noncovalent interactions during the ExD process implies that higher order protein structure should also survive, and have some effect on the observed dissociation pattern.…”
Section: Supplemental Activation Facilitates Cleavage Of the C(α)-c(βmentioning
confidence: 99%
“…p53 plays acrucial role in cancer prevention and is often referred to as the "guardian of the genome". These include cryoelectron microscopy (EM), [4] native mass spectrometry (MS), [5] ion mobility mass spectrometry (IM-MS), [6] and cross-linking/MS. [2] Thes tructural elucidation of IDPs is increasingly being recognized as an important task in structural biology,considering the high prevalence of proteins containing intrinsically disordered regions.…”
mentioning
confidence: 99%
“…[1] p53 is one of the most studied and prominent representatives of intrinsically disordered proteins (IDPs). These include cryoelectron microscopy (EM), [4] native mass spectrometry (MS), [5] ion mobility mass spectrometry (IM-MS), [6] and cross-linking/MS. [2] However,o wing to their lack of ad efined three-dimensional structure,I DPs pose ah uge challenge for classical structure elucidation methods,s uch as X-ray crystallography or NMR spectroscopy.C urrently,t he method of choice for 3D-structure analysis of IDPs is NMR, [3] but alternative techniques have recently been developed and are under continuous improvement.…”
mentioning
confidence: 99%